2021
DOI: 10.1111/epi.16915
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation rescues valproic acid‐induced developmental neurotoxicity and behavioral alterations in zebrafish embryos

Abstract: Objective: Fetal exposure to the anticonvulsant drug valproic acid (VPA), used to treat certain types of epilepsy, increases the risk for birth defects, including neural tube defects, as well as learning difficulties and behavioral problems. Here, we investigated neurotoxic effects of VPA exposure using zebrafish as a model organism. The capacity of folic acid (FA) supplementation to rescue the VPA-induced neuronal and behavioral perturbations was also examined. Methods: Zebrafish embryos of different transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Studies have found that FA has a protective effect on the neurotoxicity of VPA ( Muhsen et al, 2021 ), we hypothesized that FA is a feasible candidate for preventing VPA-induced embryonic neurogenesis abnormalities. To further investigate whether FA supplementation could ameliorate the VPA-induced negative effect, we cotreated hPSCs with VPA1 μM and FA10 μM, defined as FV group ( Supplementary Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that FA has a protective effect on the neurotoxicity of VPA ( Muhsen et al, 2021 ), we hypothesized that FA is a feasible candidate for preventing VPA-induced embryonic neurogenesis abnormalities. To further investigate whether FA supplementation could ameliorate the VPA-induced negative effect, we cotreated hPSCs with VPA1 μM and FA10 μM, defined as FV group ( Supplementary Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Both models are relatively high throughput for in vivo work and would make an excellent platform for testing the effect of multiple micronutrients independently or together. For example, it was recently shown that zebrafish embryos exposed to VPA had smaller midbrains and hindbrain midline gap; however, when the VPA-treated embryos were also given folic acid the brain size increased, and midline gap decreased (Muhsen et al, 2021). Although NTC in these models does not mimic human NTC as well as mouse, the relative quickness and accessibility make them an excellent model to test many conditions (Nikolopoulou et al, 2017).…”
Section: Looking Forward In Studying Gene-environment Interactions In Ntdsmentioning
confidence: 99%
“…VPA has been known to be teratogenic since the early 1980s 34 and exposure to VPA during human embryo development has been found tightly linked to neural tube defects 35 and malformations in the midbrain and hindbrain 38,39,50,51 , as well as neurological disorders such as severe cognitive defects, autism spectrum disorder, and schizophrenia 52,53 . Recently, cytoskeletal protein MARCKSL1, which is an actin-stabilizing protein essential for dendrite morphogenesis and synapse maturation, has been identified to mediate VPA-induced morphological defects in developing neurons 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Several teratogens have been identified that disrupt the midbrain/hindbrain development [34][35][36][37] . For example, valproic acid (VPA) exposure during embryo development causes neural tube defects and other types of malformations such as smaller midbrain size and an increase in the midline gap of the hindbrain 38,39 . It also decreases the proliferation of neuronal progenitor cells in early development 38 .…”
Section: Drug-induced Developmental Defects In Early Midbrain and Hin...mentioning
confidence: 99%
See 1 more Smart Citation